What Interventions Do Physical Therapists Provide for Patients With Cardiorespiratory Conditions, Neurological Conditions, and Conditions Requiring Acute Hospital Care? A Systematic Review. Issue 7 (14th April 2020) - Zadro, Joshua R; Cheng, Sonia; O'Keeffe, Mary; Maher, Christopher G
Abstract: Objective: The aim of this systematic review was to determine what percentages of physical therapists provide interventions that are of high value, low value, or unknown value for cardiorespiratory conditions, neurological conditions, or conditions requiring acute hospital care. Whether an intervention was considered high or low value was determined by reference to guidelines or systematic reviews. Methods: Searches of numerous databases were performed by combining terms synonymous with "practice patterns" and "physical therapy" until April 2018. Studies that investigated what interventions physical therapists provide for any cardiorespiratory condition, neurological condition, or condition requiring acute hospital care through surveys and audits of clinical notes were included. Through the use of medians and interquartile ranges, the percentages of physical therapists who provided interventions that were of high value, low value, or unknown value were summarized. Results: Twenty-six studies were included. The median percentages of physical therapists who provided interventions of high, low, and unknown value for chronic obstructive pulmonary disease ranged from 78% to 96%, 67% to 100%, and 56% to 91%, respectively. These percentages ranged from 61% to 97%, 87% to 98%, and 83% to 98% for adults who were critically ill in intensive care units; 70% to 93%, 38% to 50%, and 8% to 95% before or after cardiac/thoracic surgery; 25% to 96%, 23% to 84%, and 96% for acute stroke; and 11% (high value) and 13% (unknown value) for Parkinson disease, respectively. Conclusions: This review found patterns of physical therapist practice for cardiorespiratory conditions, neurological conditions, and conditions requiring acute hospital care that were both evidence based and not evidence based. A concern is that a substantial percentage of physical therapists provided interventions that were of low or unknown value despite the availability of high-value interventions. Impact: This systematic review is the first, to our knowledge, to summarize the percentage of physical therapist treatment choices that were high versus low value for cardiorespiratory conditions, neurological conditions, and conditions requiring acute hospital care. The findings highlight areas of practice where low-value care could be replaced with high-value care—such as in the management of patients who have chronic obstructive pulmonary disease or who are in intensive care—and identify an urgent need to develop and test strategies to ensure that patients with these conditions receive the interventions most likely to improve their outcomes.